2023
DOI: 10.1039/d3cc01126g
|View full text |Cite
|
Sign up to set email alerts
|

Formation of lanthanide luminescent di-metallic helicates in solution using a bis-tridentate (1,2,3-triazol-4-yl)-picolinamide (tzpa) ligand

Abstract: The chiral bis-tridentate (1,2,3-triazol-4-yl)-picolinamide (tzpa) ligand 1 was used in the formation of di- and triple stranded lanthanide based di-metallic helicates in acetonitrile solution, where the changes in the ground...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…1g, Tb-BPDC, when excited at 312 nm, displayed distinct green emissions at 491, 545, 585, and 621 nm. 19 These emissions were correlated with specific electronic transitions, notably 5 D 4 -7 F J ( J = 6, 5, 4, 3), inherent to Tb 3+ ions. Among these, the 5 D 4 -7 F 5 transition was particularly pronounced, emphasizing its significant luminescence activity.…”
mentioning
confidence: 90%
“…1g, Tb-BPDC, when excited at 312 nm, displayed distinct green emissions at 491, 545, 585, and 621 nm. 19 These emissions were correlated with specific electronic transitions, notably 5 D 4 -7 F J ( J = 6, 5, 4, 3), inherent to Tb 3+ ions. Among these, the 5 D 4 -7 F 5 transition was particularly pronounced, emphasizing its significant luminescence activity.…”
mentioning
confidence: 90%
“…Following this strategy, enantiomer pairs of Eu 3+ complexes for both the i Pr and Ph-PyBox derivatives were synthesized (Scheme ). On one hand, PyBox ligands have shown to be suitable chirality inducers in both homo- and heteroleptic complexes. On the other hand, Maury et al showed that the strategy of ligands with extended conjugation and strong push–pull systems with varying charge-transfer character provides high 2PE cross sections in the case of dipicolinic acid derivatives. ,, …”
Section: Introductionmentioning
confidence: 99%